2006
DOI: 10.1088/0268-1242/22/1/s35
|View full text |Cite
|
Sign up to set email alerts
|

High-density plane deposition kinetics and facet propagation in silicon-selective epitaxial growth

Abstract: This paper reports morphological results and kinetics of the main high-density planes obtained after silicon growth on two different etched figures exhibiting the {3 1 1} and/or {1 1 1} planes. These etched profiles were generated by HCl chemical vapour etching on SiO 2 -patterned wafers with the (0 0 1) orientation. Deposition was performed after SiO 2 removal on a full-sheet wafer with a chlorinated chemistry. Scanning electron microscope observations after silicon growth at temperatures between 700 • C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Several studies reported for both growth and etching processes from the vapor phase showed that the morphology and roughness of the incipient thin films strongly depend on the substrate surface roughness, surface ripples, and faceting, and it is a strong concern in selective epi-growth technologies. Moreover, Dutartre et al reported that lateral epitaxial overgrowth and epi rounding in narrow lines is strongly controlled by substrate microfaceting effects and slow-growing crystal facets in the Si(100)/SiGe system …”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported for both growth and etching processes from the vapor phase showed that the morphology and roughness of the incipient thin films strongly depend on the substrate surface roughness, surface ripples, and faceting, and it is a strong concern in selective epi-growth technologies. Moreover, Dutartre et al reported that lateral epitaxial overgrowth and epi rounding in narrow lines is strongly controlled by substrate microfaceting effects and slow-growing crystal facets in the Si(100)/SiGe system …”
Section: Introductionmentioning
confidence: 99%
“…The total pressure was adjusted to 2000 Pa for both materials. {1 1 1} plane creation at pattern edge is favoured [14]. Then, the SiO 2 hard mask is removed via a conventional HF-wet clean and finally the {1 1 3} plane is created thanks to a Si HT n-SEG (850 1C).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for both materials, a similar kinetics ranking, defined as GR 111 oGR 113 oGR 001 (GR hkl ¼Growth Rate of corresponding plane), is observed and seems to equalize at low temperature. Therefore, the growth kinetics anisotropy can be characterized by the ratio r hkl , which is defined by the growth rate of corresponding (hkl) plane (GR hkl ) divided by the growth rate of (0 0 1) surface (GR 001 ): r hkl ¼GR hkl / GR 001 [23]. This ratio is plotted on the respective offset graph.…”
Section: Growth Kinetics Anisotropymentioning
confidence: 99%
“…The advantage of this profile is the absence of a focal point of stress and close proximity of the stressed layer to Si channel. The drawback is that numerous facets are exposed, where the different growth rates on different crystallographic planes play an important role [16][17].…”
Section: Morphology Considerations Of Different Crystallographic Orie...mentioning
confidence: 99%
“…The choice of the Si substrate surface orientation and the channel direction has consequences on the carrier mobility [15] as well as on the growth kinetics [16,17] and etch kinetics [18] of the SiC:P films since different crystallographic planes become exposed in the formed recess. Some aspects of surface preparation prior to epi deposition and possible resulting problems have been described previously [14].…”
Section: Introductionmentioning
confidence: 99%